Massively parallel sequencing as an investigative tool. Issue 6 (2nd November 2021) - Ryan, Luke; Mathieson, Megan; Dwyer, Tegan; Edwards, Marcus; Harris, Libby; Krosch, Matt; Power, Daniel; Brisotto, Paula; Allen, Cathie; Taylor, Ewen
ABSTRACT: This research was designed to assess the operational effectiveness of Biogeographical Ancestry (BGA) and Externally Visible Characteristics (EVCs) Massively Parallel Sequencing (MPS) for criminal cases. Engaging with end users to assess new DNA technology is a novel approach for Queensland, and considered necessary given the investment required to develop this capability. Detectives were presented with MPS intelligence from four real Queensland criminal cases in a workshop setting, and were asked to assess its utility. Detectives were also asked to determine whether they could use the MPS intelligence to prioritize (include/exclude) persons of interest (POIs). The results from this research showed the detectives had confidence in MPS intelligence and its value in providing avenues for investigation. There was a high rate of correct interpretation and use of the MPS results; however, the frequency of errors suggest that detectives need support from a trained forensic biologist to ensure accurate result interpretation. Detectives excluded on average 30% of POIs, demonstrating the potential use of MPS intelligence to prioritize POIs. Although this workshop did not accurately replicate an active criminal investigation, the results of this research are encouraging and suggest that MPS intelligence is operationally effective and could be used in Queensland as a valuable investigative tool.